PERAN GURU DAN ORANG TUA DALAM MEMBENTUK KARAKTER JUJUR PADA ANAK - Nunung Dian Pratiwi (Universitas Islam Nahdlatul Ulama Jepara, 2021)
There is dishonesty that is endemic in society, namely a lot of hoax news, hate speech, prejudice, cheating, corruption, theft, fraud, robbery so that it has an impact on anxiety, mutual suspicion and disharmony in social life. This happens because the formation of honest character in children is not successful by teachers at school and parents at home. The formation of the character of honesty in children in the family is very important. Family is the first environment in which children grow, develop and build a personality that will become their identity in the future. Exemplary and direct examples of honesty by parents will stick in the child's memory. Getting children to be honest with themselves is the beginning of forming honesty for their living capital. The intensity of the presence, caresses of affection, warmth and attention given by parents to children plays an important role in forming an honest character. Teachers also play an important role in shaping honest character in children at school by giving examples and honest behavior. Therefore, this study aims to describe how the roles of teachers and parents shape honest characters in children. The stages of character building will be correlated with psychological theory. The results of the study found that forming an honest character, children are not only equipped with cognitive knowledge about honesty, but also have to arrive at the affective realm and be integrated into real behavior.Keywords : Teachers Role, Parents Role, Character, Honest